Burns Injuries Among In-patients at Moi Teaching and Referral Hospital, Eldoret, Kenya - Lelei, L. K.; Chebor, A. K.; Mwangi, Henry R. (The Surgical Society of Kenya, 2011)
Background: Africa contributes 12.2% to the total global deaths due to burn injuries. There are no data on burns in the Western region of Kenya Objectives: To determine the causes and outcome of burns injuries among in-patients at Moi Teaching and Referral Hospital (MTRH), Eldoret, Kenya. Study design: Retrospective Cross-sectional study. Setting: The surgical wards of MTRH, an 800 bed tertiary teaching and referral hospital in the Western region of Kenya. Results: The age ranged between 4 days and 79 years (mean 7.9±13.7 years).The male to female ratio was 1.5:1. The common causes of burn injury were scalds and open fire. The mean duration of hospitalization was 25.7 ±33.5days (Range 1 to 256 days). The mortality rate was 5%. Conclusion: Scalding is the leading cause of burns at MTRH. The length of hospitalization and mortality rate are comparable to those of the developing world.
Keywords: Burns injuries; in-patients; Kenya